An enhanced open sandwich immunoassay by molecular evolution for noncompetitive detection of Alternaria mycotoxin tenuazonic acid. (1st November 2021) - Liang, Yifan; Wang, Yu; Wang, Feng; Li, Jiadong; Wang, Chenglong; Dong, Jinhua; Ueda, Hiroshi; Xiao, Zhili; Shen, Yudong; Xu, Zhenlin; Wang, Hong
Graphical abstract: Highlights: A new assay with OS-ELISA for the detection of tenuazonic acid was developed. The interaction between antibody V region fragments against tenuazonic acid was studied. Mutation at VH 39 reduced the background and increased the assay sensitivity. By using MBP-VL instead of L chain, a SC50 value of 2.60 ng/mL for tenuazonic acid was attained. Abstract: Open sandwich enzyme-linked immunosorbent assay (OS-ELISA), a novel noncompetitive immunoassay format, has shown great potential in rapid detection for small molecules compared with traditional competitive format. Here, an enhanced OS-ELISA towards the mycotoxin tenuazonic acid (TeA) was developed for the first time based on heavy chain variable region (VH ) and light chain variable region (VL ) from the hybridoma cells (3F10) producing anti-TeA monoclonal antibody (mAb). The established OS-ELISA exhibited a limit of detection of 0.08 ng/mL, and was 13 times more sensitive than mAb-based indirect competitive ELISA (ic-ELISA). The proposed assay was also applied to detect TeA contents in juice, flour and tomato ketchup samples with satisfactory recoveries of 87.6%–111.3%. Finally, the great accuracy of the established OS-ELISA method was validated by the standard ultra-performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS).